PENINGKATAN KARAKTER TOLERANSI MELALUI PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN DI SEKOLAH DASAR (SD) - Alisa Marta Boimau; Dion Stefen Adu; Jenaris Tameon; Jesi Ottu; Verli Chayren Oematan; Vira bella dja Persulessy (CV. Adiba Aisha Amira, 2025)
Christian Religious Education (PAK) plays an important role in shaping the character of tolerance in the elementary school (SD) environment in Indonesia, which is known as a country with cultural, religious, and ethnic diversity. This study aims to provide an overview of how Christian religious education can enhance attitudes of tolerance through the teaching and application of Christian values, which involve the role of teachers, and school culture that involves all aspects of primary school. Through a review of four journals, it was found that PAK not only functions as a teaching of religious values, but also as a forum to instill empathy, respect for differences, and social concern. Teachers also actively play a role as facilitators and role models are essential in the learning process, while a supportive school culture and positive activities in schools contribute to the establishment of a harmonious and peaceful environment. Despite challenges in the implementation of PAK, such as a lack of resources and training for teachers, recommendations for more inclusive curriculum development and ongoing training for educators are urgently needed. The results of this research are expected to provide insight into the development of tolerance character education in elementary schools, as well as create a young generation that is ready to face the challenges of diversity in the future.